A new statistic for regression transformation - YANG, Zhenlin (Institutional Knowledge at Singapore Management University, 2000)
A new statistic for testing a regression transformation is proposed based on a result of Yang (1999). This statistic is shown to be stable, having a null distribution almost independent of model type and parameter values, accurate and easy to implement. The statistic is of the Wald-type and thus is compared with the Wald statistic given by Lawrence (1987) in terms of size, null distribution and power using simulation. The simulation results show that the new statistic generally outperforms that of Lawrence.